The contrasting roles of water and dust in controlling daily variations in radiative heating of the summertime Saharan Heat Low - Marsham,JH; Parker,DJ; Todd,MC; Banks,JR; Brindley,HE; Garcia-Carreras,L; Roberts,AJ; Ryder,CL (Atmospheric Chemistry and Physics Discussions, 2015)
The summertime Sahara Heat Low (SHL) is a key component of the West African Monsoon (WAM) system. Considerable uncertainty remains over the relative roles of water vapour and dust aerosols in controlling the radiation budget over the Sahara and therefore our ability to explain variability and trends in the SHL, and in turn, the WAM. Here, new observations from the Fennec field campaign during June 2011 and June 2012, together with satellite retrievals from GERB, are used to quantify how total column water vapour (TCWV) and dust aerosols (from aerosol optical depth, AOD) control day-to-day variations in energy balance in both observations and ECWMF reanalyses (ERA-I). The data show that the earth-atmosphere system is radiatively heated in June 2011 and 2012. It is TCWV that largely determines variations in daily mean TOA net flux and the net heating of the earth-atmosphere system. In contrast, dust provides the primary control on surface heating, but the decreased surface heating from dust is largely compensated by increased atmospheric heating, and so dust control on net TOA radiation is weak. Dust and TCWV are both important for direct atmospheric heating. ERA-I captures the control of TOA net flux by TCWV, with a positive correlation (r = 0.6) between observed and modelled TOA net radiation, despite the use of a monthly dust climatology in ERA-I that cannot capture the daily variations in dustiness. Variations in surface net radiation, and so the vertical profile of radiative heating, are not captured in ERA-I, since it does not capture variations in dust. Results show that ventilation of the SHL by cool moist air leads to a radiative warming, stabilising the SHL with respect to such perturbations. It is known that models struggle to capture the advective moistening of the SHL, especially that associated with mesoscale convective systems. Our results show that the typical model errors in Saharan water vapour will lead to substantial errors in the modelled TOA ener